Controlling the reaction kinetics of sodium carbonate-activated slag cements using calcined layered double hydroxides. (March 2016) - Ke, Xinyuan; Bernal, Susan A.; Provis, John L.
Abstract: In this study, Na2 CO3 -activated slag cements were produced from four different blast furnace slags, each blended with a calcined layered double hydroxide (CLDH) derived from thermally treated hydrotalcite. The aim was to expedite the reaction kinetics of these cements, which would otherwise react and harden very slowly. The inclusion of CLDH in these Na2 CO3 -activated cements accelerates the reaction, and promotes hardening within 24 h. The MgO content of the slag also defines the reaction kinetics, associated with the formation of hydrotalcite-type LDH as a reaction product. The effectiveness of the CLDH is associated with removal of dissolved CO3 2 − from the fresh cement, yielding a significant rise in the pH, and also potential seeding effects. The key factor controlling the reaction kinetics of Na2 CO3 -activated slag cements is the activator functional group, and therefore these cements can be designed to react more rapidly by controlling the slag chemistry and/or including reactive additives.